Multidisciplinary home-based interventions in adverse events and quality of life among frail older people: A systematic review and meta-analysis - Marta Carolina Ruiz-Grao; Celia Álvarez-Bueno; Miriam Garrido-Miguel; Carlos Berlanga-Macias; Marta Gonzalez-Molinero; Beatriz Rodríguez-Martín (Heliyon)
Objective: To determine the effects of multidisciplinary home-based interventions delivered by multidisciplinary teams to prevent adverse events (mortality, emergency visits, and hospital readmissions) and improve quality of life (QoL) among frail older adults. Methods: A systematic search of PubMed/MEDLINE, Scopus, the Cochrane Central Register of Controlled Trials, Web of Science, and the Cumulative Index to Nursing and Allied Health Literature was conducted until November 2023. The Risk of bias of the randomized controlled trials was assessed via the Cochrane risk of bias tool (RoB 2.0), and the synthesis and quality of evidence for each outcome were assessed via the Grading of Recommendation, Assessment, Development and Evaluation (GRADE). The effect size (ES), pooled OR (p-OR), and 95 % confidence intervals (95 % CIs) were calculated for QoL and adverse events. Subgroup analyses and meta-regressions were conducted. Results: Twenty-seven studies were included in the systematic review. The p-OR for the effect of home-based interventions on mortality was 0.88 (95 % CI: 0.75 to 1.02; I2 = 27.6 %), that for visits to the emergency department was 0.88 (95 % CI: 0.78 to 1.00; I2 = 56.4 %), that for hospital admissions in days was 0.85 (95 % CI: 0.52 to 1.37; I2 = 85.2 %), and that for hospital admissions was 0.90 (95 % CI: 0.79 to 1.01; I2 = 52.0 %). In addition, the pooled ES for the effect of home-based interventions on QoL was 0.08 (95 % CI: 0.02 to 0.17; I2 = 60.7 %). The type of intervention, type of control, evaluation of the risk of bias, duration of the intervention, mean age of the intervention group, and percentage of women in the intervention group did not modify the effect of MHBIs to prevent adverse events or to improve quality of life (QoL) among frail older adults. Conclusions: Multidisciplinary home-based interventions do not appear to reduce adverse events (mortality, visits to the emergency department, or hospital admissions/readmissions) in older people defined and/or considered frail. In addition, these interventions do not improve QoL in older people, or the evidence is unclear.